Girls and women of color in STEM : navigating the double bind in K-12 education - Polnick, Barbara; Irby, Beverly J.; Ballenger, Julia, 1949-; Abdelrahman, Nahed (Research on women and education., 2020)
"At no time in our period in history is it more important for us to engage the untapped resource of women of color in today's workforce, specifically in the fields of science, technology, engineering, and mathematics (STEM). Girls and women of color bring culturally different understandings and experiences that can be leveraged to innovatively solve complex problems. It is both timely and imperative that education and career efforts work to build the capacity of girls and women of color to advance in STEM fields. This book is a culmination of research on the issues and challenges (and successes!) for girls and young women in the fields of science, technology, engineering, and mathematics (STEM). Authors in these thirteen chapters share their research on the impact of current practices in schools and related educational settings, as well as effective interventions that illustrate ways to assist and promote girls and women of color to navigate the double bind in STEM fields today. The chapters address issues experienced across multiple ethnicities and races and span a broad range of settings from early childhood to high school to higher education. The book is organized around two parts: those studies focused on partnerships and professional development outside the school walls and those studies of girls and young women of color within schools"--